LKPD Kontekstual Berbasis Pondok Pesantren untuk Menunjang Pemahaman Peserta Didik pada Materi Aritmatika Sosial - Satiti, Wisnu Siwi; Fitriah, Khurrotul; Nasrulloh, M. Farid (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2021)
Nowadays, more and more real-life situations require some level of mathematical understanding. This shows the importance of mathematics in everyday life. One of the mathematical studies that is widely used in everyday life is social arithmetic. However, the practice of social arithmetic teaching has not accommodated these needs, especially for students who are also students in Islamic boarding schools (pondok pesantren). Considering this, in this study a learning media was developed in the form of Student Worksheets (LKPD) to support students' understanding of social arithmetic. The target of this study is students who are also students in Islamic boarding schools. Therefore, LKPD was developed contextually based on Islamic boarding schools’ life situations. This study uses the Research and Development (R&D) method with the ADDIE model. This study aims to develop contextual worksheets based on Islamic boarding schools on social arithmetic. The results showes that the LKPD developed was valid and practical. The results of implementing the product in the classroom shows that the use of this LKPD supports students' understanding of social arithmetic. The use of LKPD also receives a